Bird diversity, composition and response during COVID-19 in an urban landscape, Jamalpur, Bangladesh (Dhaka University Journal of Biological Sciences, 2021)
The world has been encountering a COVID-19 pandemic since late 2019. The world’s people have also witnessed the free movement of wildlife, even in many urban areas in some countries during the imposed lockdown. We conducted research on the birds in the urban landscape of Jamalpur Sadar upazila from March 2020 to October 2020 during this pandemic situation. A total of 134 species of birds with 4338 individuals were recorded during the study period. The number of resident bird species was the maximum (115 species, 85.82%) compared to migrants. The highest number of birds was observed (120 species, 89.55%) and counted 2278 individual birds 52.51%) in the summer season. It was observed that the highest diversity of birds (89 species, 65.92%) was in March. The tree was the most (94 species, n = 2502) used microhabitat by birds in the study area. Among all birds, Pycnonotus cafer was the most abundant bird species with the highest relative abundance (6.11%). Some bird species (e.g. Metopidius indicus, Anastomus oscitans, Amaurornis phoenicurus, Streptopelia tranquebarica, Lonchura malacca) were frequently observed in the urban landscape of the study area during the pandemic. Proper management and awareness creation are essential for the conservation of the bird species in this area.Dhaka Univ. J. Biol. Sci. 30(2): 261-274, 2021 (July)